Managing quality in industrial companies: the empirical study of quality management systems in the Czech Republic - Ondra, Pavel (Serbian Journal of Management, 2021)
Since monitoring, managing, sustaining and improving the quality are is so important to the competitiveness of the company, it is advisable to use a variety of Quality Management tools (QMTs) and techniques, in addition to comprehensive Quality Management Systems (QMSs). The main aim of this research study is to explore the connection between Quality Management System (QMS) and selected Quality Management tools (QMTs) in industrial companies in the Czech Republic. This study summarizes the results of the online questionnaire survey between April 2017 and July 2017. The final sample consisted of answers from 200 companies. It has been found that 46% of surveyed companies monitor and evaluate quality of their business processes. Furthermore, it has been found that 59% of surveyed companies are ISO 9001 certified. Larger companies tend to monitor and evaluate quality of their business processes and to have ISO 9001 certification. The relationships between the use of Quality Management tools (QMTs), monitoring and quality assessment of business processes (MQABP) and ISO 9001 certification have been found based on the Pearson's Chi-square Test of Independence, the Fisher's Exact Test of Independence and the Column Proportions Z-Test.
Keywords: Quality Management; Quality Management Tools; Quality Management System; Industrial Companies; Czech Republic